2013
DOI: 10.1088/0953-2048/26/9/095006
|View full text |Cite
|
Sign up to set email alerts
|

The critical current density of grain boundary channels in polycrystalline HTS and LTS superconductors in magnetic fields

Abstract: We provide evidence that a single mechanism-flux flow along channels-can explain the functional form of the critical current density (J c) in the low temperature superconductor Nb 3 Sn and in the high temperature superconductors (HTS) YBa 2 Cu 3 O 7-δ (YBCO) and (Bi,Pb) 2 Sr 2 Ca n-1 Cu n O x (BiSCCO) in low and high magnetic fields. In this paper, we show that standard flux pinning theories, used for the last four decades to describe J c in low temperature superconductors (LTS), cannot explain the strain depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 74 publications
7
42
0
Order By: Relevance
“…We are putting significant effort into developing the mathematical framework for flux flow along channels. As the community develops better experimental tools to measure the local structural and chemical homogeneity along 29 channels between pinning sites, and completes more comprehensive Ic measurements on many different samples, we expect that it will become increasingly apparent that the local properties of the channels, along which flux flows, will need to be explicitly included in any accurate description of current density [43,44].…”
Section: F-valuesmentioning
confidence: 99%
“…We are putting significant effort into developing the mathematical framework for flux flow along channels. As the community develops better experimental tools to measure the local structural and chemical homogeneity along 29 channels between pinning sites, and completes more comprehensive Ic measurements on many different samples, we expect that it will become increasingly apparent that the local properties of the channels, along which flux flows, will need to be explicitly included in any accurate description of current density [43,44].…”
Section: F-valuesmentioning
confidence: 99%
“…Under θ=0° (B//c-axis), however the I c is significantly affected by the magnetic field. Recently, Sunwong et al reported that the strain effect on J c in YBCO is related to its induced change in the grain boundaries properties [51]. Since the irreversibility in I c is attributed to a presence of permanent deformation or fracture in REBCO coating film such as micro cracks, these will likely affect the correlated pinning under B//c-axis such as grain boundary effect.…”
Section: Strain Effect On I C Under Magnetic Field I C (ε B)mentioning
confidence: 99%
“…The intensity and frequency of the stress/strain applied to the CC tapes depends on the specific performance condition of the device. In this cyclic loading, the tapes were tested up to failure and in other case up to 10 6 cycles in order to determine the electrical fatigue limit of EDDC-SmBCO CC tapes, i. e., with the 95% I c retention [51]. From this criterion, the electrical fatigue limit was determined to be about 500 MPa (0.85σ y ) in Fig.…”
Section: Cyclic Loading (Fatigue)mentioning
confidence: 99%
“…We have long known that although characterizing grain boundary pinning using just the size of the grains is useful for describing similar superconducting materials with different grain sizes 35 , it is very simplistic. Visualisation of solutions to the TDGL equations 14 for polycrystalline materials has shown that fluxons cross the superconductor by flowing along the grain boundaries 36 37,38 .…”
Section: Concluding Comments and Future Workmentioning
confidence: 99%